The limitations of the right to be heard in disciplinary proceedings against public servants in Malaysia: an infringement of the fundamental liberties under Article 5 and Article 8 of the Federal Constitution - Zukiferee Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Since 1976, despite the Privy Council’s decision in Najar Singh’s case, the right to be heard particularly on its expansion to the right of oral hearing in disciplinary proceedings against public servants in Malaysia has become an ongoing challenge. This is the outcome of the different approaches adopted by the courts in determining such right to the affected public servants. This article analysed the constitutional provisions and the judicial review approach with regards to the right to be heard of public servants in disciplinary proceedings as granted in Article 135(2) of the Federal Constitution. This article employed qualitative method by using content analysis. The findings indicated that first, the interpretation of the constitutional term “a reasonable opportunity of being heard” is vague. Next, the judicial review application is inconsistent and finally, the limitation of the right to be heard deprives the life and personal liberty of a person as envisaged in Article 5 and Article 8 of the Federal Constitution. Thus, the constitutional protection of “a reasonable opportunity of being heard” which falls under Article 135(2) in the case of dismissal and reduction of a public servant’s rank in Malaysia should be interpreted in the light of the fundamental liberties as guaranteed in Article 5 and Article 8 of the Federal Constitution. It is proposed that the oral hearing which is an essence to the principle of right to be heard be regulated in the disciplinary proceedings against public servants in Malaysia.